Early Periprosthetic Joint Infection Rates Following Total Hip and Knee Arthroplasty: A Single-Center Study - Aslan, Lercan; Gedik, Cemil Cihad; Karaismailoğlu, Bedri; Özşahin, Mahmut Kürşat; Kaynak, Gökhan; Öztürk, Recep; Aydıngöz, Önder (Cerrahpaşa Medical Journal, 2023)
Objective: Periprosthetic joint infections are one of the frightening complications of total joint arthroplasty. This complication has devastating effects on patients, and the acute ones are mostly healthcare-associated and preventable. In this clinical study, we aimed to determine the incidence of acute periprosthetic joint infections in primary total hip arthroplasty (THA) and primary total knee arthroplasty (TKA) cases performed over 1 year in our tertiary referral center. Methods: Between February 15, 2015, and February 16, 2016, 212 arthroplasty surgeries were performed, of which 89 procedures were THA and 123 were TKA. In addition, the operating room infrastructure and patient preparations were made following the guidelines for diagnosing and preventing periprosthetic joint infections published in 2013, and cooperation was established with the Infection Committee of Cerrahpaşa Faculty of Medicine. Results: The mean age of the patients who underwent THA was 51.7 (minimum: 16; maximum: 90), and the mean age of the patients who underwent TKA was 65.3 (minimum: 30; maximum: 85). One of the THA (1.1%) and 3 of the TKA (2.4%) patients were diagnosed with early periprosthetic joint infection and treated accordingly. When all hip and knee arthroplasties were evaluated together, the total infection rate was 1.8%. Conclusion: Our results were similar to the results of other incidence-indicating publications. The preventive measures mentioned in the guidelines such as the use of mupirocin and the application of a chlorhexidine bath before the day of the surgery, reducing the transfusion rates by application of tranexamic acid, and the use of chlorhexidine and povidone-iodine together for surgical site cleaning were taken in our clinic to decrease the early periprosthetic joint infection rate. Cite this article as: Aslan L, Cihad Gedik C, Karaismailoğlu B, et al. Early periprosthetic joint infection rates following total hip and knee arthroplasty: A single-center study. Cerrahpaşa Med J. 2023;47(3):264-269.